Analisis Efektivitas Pendayagunaan Dana Zakat Pada Program Bedah Rumah Tidak Layak Huni Oleh BAZNAS Kabupaten Tanjung Jabung Barat - Harry Ratul Jannah; Rafiqi .; Aditya Pratama (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2025)
This research aims to gain an understanding of the condition of recipients of the uninhabitable house renovation program by BAZNAS West Tanjung Jabung Regency, analyzing the impact on recipients and the effectiveness of the program. The type of research used is descriptive qualitative research, data collected and obtained through interviews, observation and documentation. Data validity test using extended observation techniques, triangulation and reference materials. The results of this research show that the BAZNAS West Tanjung Jabung Regency renovation program for uninhabitable houses is said to be effective by using 4 benchmarks or aspects, namely the task aspect, plan aspect, regulatory aspect and goal aspect, and shows that this program has a good impact on the lives of mustahik.